The impact of management control systems on performance of Malaysian local authorities - Ilias, Norazlina; Abdulatiff, Nik Kamaruzaman; Mohamed, Nafsiah (2015)
An increasing number of profit and non-profit organizations implementing management control systems (MCSs) have proven the importance of the systems in improving organizational performance. However, there is a lack of empirical evidence concerning how the MCSs affect the performance of local authorities.Even though there are some previous studies concerning the performance of local authorities, most only focus on performance measurement methods, such as the use of balanced scorecard and performance indicators.The application of MCSs and their effect on performance are rarely discussed in local authorities, especially in the Malaysian environment.Therefore, the objective of this study is to examine the impact of MCSs on performance of Malaysian local authorities by using the structural equation modeling (SEM) tool. Statistical results showed that the internal formal control were significantly associated with all three performance dimensions – financial, service quality, and procedural, as expected. However, the internal informal control only had a direct relationship with the service quality performance, and did not have a significant relationship with the financial performance and procedural performance.This study contributes to the literature concerning the structural linkage among internal controls and performance constructs within Malaysian local authorities by developing and testing the hypothesized relationships using SEM analysis.